The origin and localization of selected metabolic pathways in marine diatoms - Jiroutová, Kateřina (Jihočeská univerzita, 2009)
Sequenced diatoms Thalassiosira pseudonana and Phaeodactylum tricornutum belong to the chromist algae harboring secondary plastids, which display distinct evolutionary history when compared to photosynthetic organelles from rhodophytes, green algae and plants. Via secondary endosymbiosis, heterotrophic eukaryotic ancestor of diatoms engulfed red alga, and in addition to the new organelle, it obtained fitness increasing peculiarities in the chimerical cell metabolism and lifestyle. We examined phylogeny and in silico localization of the nuclear-encoded but plastid located enzymes of tryptophan biosynthesis. We suggest that the diatom tryptophan pathway represents an extreme in the trend of plastid (cyanobacterial) enzymes to be replaced by eukaryotic isoforms. In addition, the gene napped during the endosymbiotic gene transfer from the diatom plastid genome to the diatom nucleus (psb28) was described.
The origin and localization of selected metabolic pathways in marine diatoms
Keywords: diatom-chromalveolate-endosymbiotic gene transfer-tryptophan biosynthesis-plastid-secondary endosymbiosis; diatom-chromalveolate-endosymbiotic gene transfer-tryptophan biosynthesis-plastid-secondary endosymbiosis